2017
DOI: 10.1001/jamapediatrics.2017.0745
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Receipt of Buprenorphine and Naltrexone for Opioid Use Disorder Among Adolescents and Young Adults, 2001-2014

Abstract: IMPORTANCE Opioid use disorder (OUD) frequently begins in adolescence and young adulthood. Intervening early with pharmacotherapy is recommended by major professional organizations. No prior national studies have examined the extent to which adolescents and young adults (collectively termed youth) with OUD receive pharmacotherapy.OBJECTIVE To identify time trends and disparities in receipt of buprenorphine and naltrexone among youth with OUD in the United States. DESIGN, SETTING, AND PARTICIPANTSA retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
196
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 234 publications
(213 citation statements)
references
References 40 publications
6
196
1
Order By: Relevance
“…While the availability of medication treatment has increased substantially over the past decade, significant and persistent gaps have been well-documented, particularly in the U.S. context (Feder et al, 2017;Hadland et al, 2017;Jones et al, 2015;Morgan et al, 2018;Romo et al, 2018;Saloner and Karthikeyan, 2015). Estimates using 2012 U.S. data place the gap between treatment need and treatment capacity at nearly one million persons out of an estimated 2.3 million individuals with past-year opioid abuse or dependence (Jones et al, 2015), with evidence suggesting more pronounced disparities in rural and socioeconomically disadvantaged counties (Stein et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While the availability of medication treatment has increased substantially over the past decade, significant and persistent gaps have been well-documented, particularly in the U.S. context (Feder et al, 2017;Hadland et al, 2017;Jones et al, 2015;Morgan et al, 2018;Romo et al, 2018;Saloner and Karthikeyan, 2015). Estimates using 2012 U.S. data place the gap between treatment need and treatment capacity at nearly one million persons out of an estimated 2.3 million individuals with past-year opioid abuse or dependence (Jones et al, 2015), with evidence suggesting more pronounced disparities in rural and socioeconomically disadvantaged counties (Stein et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A large retrospective cohort study from a national commercial insurance database had similar findings [53]. They found 28% of youth ages 13 to 25 years with an opioid use disorder were started on buprenorphine or naltrexone in 2014 [53]. Within the age range of 13 to 25 years younger individuals were less likely to receive medication.…”
Section: Adolescent Opioid Use Disorder Treatmentmentioning
confidence: 78%
“…Only 18% of adolescents admitted for treatment due to heroin use in 2015 had a treatment plan that included treatment with buprenorphine/naloxone or methadone compared to 42% of adults aged 45 years and older [8]. A large retrospective cohort study from a national commercial insurance database had similar findings [53]. They found 28% of youth ages 13 to 25 years with an opioid use disorder were started on buprenorphine or naltrexone in 2014 [53].…”
Section: Adolescent Opioid Use Disorder Treatmentmentioning
confidence: 99%
“…Our findings are consistent with the existing literature that has identified intravenous drug use and opioid use as risk factors associated with OD in previous studies of young people. Since research has demonstrated medication for opioid UD decreases OD risk, and opioid use/disorder is a risk factor for OD in young people, increased research is needed to identify and address barriers to the underutilization of medication for opioid UD in young people …”
Section: Discussionmentioning
confidence: 99%